2019
DOI: 10.1039/c8nr09214a
|View full text |Cite
|
Sign up to set email alerts
|

Doping of thiolate protected gold clusters through reaction with metal surfaces

Abstract: New method to dope gold nanoclusters by using metal surfaces of silver, copper and cadmium as sources of heteroatoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 32 publications
3
48
0
Order By: Relevance
“…Possibly the slow kinetics is associated with another process, like the formation of an Au 25 (Capt) 18 -Co 2+ adduct, similar to that detected for Cu. 43 Finally, it is worth mentioning that the enhancement of VCD signals due to interaction with paramagnetic metal ions like Co 2+ has been shown to be a local effect. 24 Only the functional groups in close proximity to the metal ion give rise to enhanced signals.…”
Section: Resultsmentioning
confidence: 99%
“…Possibly the slow kinetics is associated with another process, like the formation of an Au 25 (Capt) 18 -Co 2+ adduct, similar to that detected for Cu. 43 Finally, it is worth mentioning that the enhancement of VCD signals due to interaction with paramagnetic metal ions like Co 2+ has been shown to be a local effect. 24 Only the functional groups in close proximity to the metal ion give rise to enhanced signals.…”
Section: Resultsmentioning
confidence: 99%
“… 13 23 Recently, Bürgi and co-workers reported that metal exchange reactions could also be observed between Au nanoclusters and metal foils (Ag, Cd, Cu), leading to bimetallic nanoclusters. 24 Metal migration in Ag 2 Au 25 clusters was found to occur also intramolecularly when exposed to a thiol solution. 25 Altogether, this demonstrated that in solution, the structure of doped nanoclusters is not static but evolves under different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We substituted gold atoms in fcc structured Au 28 and Au 36 Doped nanoclusters provide an ideal model for understanding the metal synergy effect at the atomic level. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, doping a specic number of hetero-metal atoms at specic positions is a great challenge in the synthesis of doped metal nanoclusters with maintained structure. [15][16][17][18][19] Metal displacement reactions based on standard electrode potentials are widely used in metal extraction and alloying.…”
mentioning
confidence: 99%